Planowany proces czy seria niefortunnych decyzji? Analiza przebiegu prywatyzacji Przedsiębiorstwa Połowów i Usług Rybackich „Koga” w Helu w latach 1986–1992 - Kubicki, Mateusz (Komunizm: System - Ludzie - Dokumentacja, 2023)
This article attempts to answer the questions on the procedure for changing the ownership structure of fishing and fishing services enterprise “Koga” [Przedsiębiorstwo Połowów i Usług Rybackich, PPiUR] in the town of Hel. For clarity, the author decided on a case study. The study, in a synthetic way, presents the overall privatization process of the “Koga” enterprise. The first part of the article discusses the position of “Koga” in the Polish People’s Republic’s fishing economy. The author analyzes fundamental indicators: fishing, averaged results per unit, landings at foreign ports, production, and employment. The second part presents the process of pumping funds into “Koga,” which took place in the years 1986–1991. From the economics of the company’s operation, there was an emphasis on increasing competitiveness and reducing costs that may lead to debt, mainly in foreign currencies, which later required on-time repayments. The third part presents the course of “Koga’s” privatization in detail. At the heart of the subsequent failure of the privatization process were: the presented procedure for the total disposal of the fleet and the establishment of new companies enfranchised using the company’s assets. The last part of the article details the process of distributing “Koga’s” assets. After the division into several smaller entities, the enterprise finally declared bankruptcy in 2002.